Prophetic Inspiration in Pseudo-Philo's "Liber Antiquitatum Biblicarum" - Levison, John R. (The Jewish quarterly review, 1995)
This paper analyzes the complex permutations of four biblical accounts of spiritual inspiration in Pseudo-Philo's "Liber Antiquitatum Biblicarum": 1 Sam 19:20-24 (Saul); Judg 3:9-11 (Kenaz, biblical Othniel); Deut 34:9 (Joshua); and Num 24:2 or LXX 23:7 (Balaam). Pseudo-Philo evinces great creativity vis-à-vis the Bible, typically garnishing elements of disparate biblical texts and fusing them together (e.g., Deut 34:9, Judg 6:34, and 1 Sam 10:6 and the inspiration of Joshua), or wittingly contradicting the Bible, as when he writes that, on one occasion, the spirit did not abide (Balaam). Other characteristics of prophetic inspiration are due less to the exegetical appropriation of biblical elements and more to the assimilation of popular Greco-Roman characteristics of inspiration, such as the inability to remember what was said or seen (Saul and Kenaz), the elevation of the mind (Balaam and Kenaz), or inflammation of mind and agitation of spirit (Joshua). The product of such exegetical liberty in a Greco--Roman milieu is a complex and varied landscape over which no single view of prophetic inspiration dominates.